EDUKASI GIZI SEIMBANG PADA ANAK TUNAGRAHITA DI SDLB-C DHARMA ASIH PONTIANAK - Fitrianingrum, Iit; Arundina Triharja Tejoyuwono, Agustina; Lestari, Desriani; Windarti, Wiwik (P3M Universitas Aisyiyah Surakarta, 2025)
The quality of life for children is largely determined by fulfilling balanced nutrition during the process of growth and development. Nutritional problems in children with special needs who have intellectual limitations tend to be obese. From the results of previous research on SDLB-C Dharma Asih children, it was found that the majority of children had over-nutritional status and were obese. Therefore, parents need a good understanding regarding the fulfillment of balanced nutrition. One method that can be used is through educational seminars regarding the fulfillment of balanced nutrition. To determine the level of knowledge of respondents, pre and posttest questionnaires were filled out. The results of the questionnaire show that there is a difference in parents' knowledge before and after providing education regarding balanced nutrition for children with special needs at SDLB-C Dharma Asih (p 0.40 < 0.05). The method used is felt to be beneficial for parents. In the future, it is hoped that more parents will be able to participate in educational activities. Another solution that can be implemented is providing education indirectly to parents through distributing leaflets or sticking up posters related to balanced nutrition and caring for children with special needs.